2016
DOI: 10.12659/msm.898138
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium and Risk of Nonmedullary Thyroid Cancer in Patients with Primary Hyperparathyroidism

Abstract: BackgroundClinical cases of nonmedullary thyroid carcinoma (NMTC) in combination with primary hyperparathyroidism (PHPT) have been reported occasionally. However, the clinical characteristics and risk factors of concomitant NMTC in PHPT patients remain unclear. This study aimed to assess the association between PHPT and NMTC, and evaluate the clinical characteristics and risk factors of NMTC in Chinese patients with PHPT.Material/MethodsThis was a retrospective cohort analysis. We reviewed the medical records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 30 publications
7
27
0
Order By: Relevance
“…These reasons could explain the higher incidence of PTC in PHPT patients than in general population [ 22 ]; however, they were inadequate to explain the stronger invasive ability of PTC in asymptomatic PHPT patients whose serum calcium and PTH were lower as we observed; and, for the 1,25-hydroxy vitamin D, although we could not test it in our hospital, previous study showed that the 1,25-hydroxy vitamin D level was lower in asymptomatic PHPT patients when compared to symptomatic PHPT patients [ 35 ]. Moreover, both previous studies and the present study showed a lower PTH and serum calcium level in the PHPT patients with concomitant PTC when compared with PHPT patients with benign thyroid lesion [ 19 , 36 ]. We therefore hypothesized that elevated PTH and calcium could promote the development of PTC; however, this effect may not be dose-dependent.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These reasons could explain the higher incidence of PTC in PHPT patients than in general population [ 22 ]; however, they were inadequate to explain the stronger invasive ability of PTC in asymptomatic PHPT patients whose serum calcium and PTH were lower as we observed; and, for the 1,25-hydroxy vitamin D, although we could not test it in our hospital, previous study showed that the 1,25-hydroxy vitamin D level was lower in asymptomatic PHPT patients when compared to symptomatic PHPT patients [ 35 ]. Moreover, both previous studies and the present study showed a lower PTH and serum calcium level in the PHPT patients with concomitant PTC when compared with PHPT patients with benign thyroid lesion [ 19 , 36 ]. We therefore hypothesized that elevated PTH and calcium could promote the development of PTC; however, this effect may not be dose-dependent.…”
Section: Discussionsupporting
confidence: 68%
“…In 2007, Zheng et al were the first to report 1 case of PTC among 22 PHPT patients who had synchronous thyroid and parathyroid surgery [ 18 ]. Xue et al found 12 PTC cases among 155 surgically treated PHPT patients in 2016 [ 19 ]. More recently, Yu et al have reported that the prevalence of PTC in thyroidectomized PHPT patients was 43.14% (22/51) in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the reported studies were made in patients with PHPT in different stages of evolution [15, 16]. In the present study, in which we included patients with symptomatic PHPT, we found a prevalence of CPT in 20%.…”
Section: Discussionsupporting
confidence: 57%
“…PTC occurs in 7 to 15% of cases and is related to risk factors as age, sex, radiation exposition, family history, among others [13]. It calls to attention that, in patients with PHPT, the prevalence of thyroid nodular disease is similar that in general population; nevertheless, CPT is more frequent than in general population [15, 16]. The high concurrence of these two diseases in the same patients may not be a coincidence; a lot of factors may connect PHTP with CPT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation